Development of cockle shell-based nanocomposite biomaterial bone paste and its effectiveness for bone repair in rabbit model - Islam, KH. Nurul (2013)
This study revealed the development of paste from cockle shell-based calcium carbonate nanoparticles and in vivo evaluation using a rabbit model. Calcium carbonate and its polymorphs from cockle shells (Anadara granosa) were characterized using variable pressure scanning electron microscope (VPSEM), a transmission electron microscope (TEM), an energy dispersive X- ray analyzer (EDXA), X-ray diffraction (XRD) and Fourier transmission infrared spectroscopy (FT-IR). Rod-like aragonite crystals of cockle shell powders were observed by both SEM and TEM. The EDXA results showed that the cockle shells contained more calcium and carbon than the commercial calcium carbonate. The FT-IR analyzes revealed the presence of carbonate groups in cockle shell powders. The FT-IR analyzes also showed the presence of aragonite in cockle shell powders. The FT-IR and XRD analyzes showed that the cockle shell powders contained aragonite. The cockle shell powders were formed with good quality calcium carbonate and contained calcium carbonate in the aragonite phase. The calcium carbonate aragonite nanoparticles were synthesized from micron sized cockle shell powders. The method involves a simple mechanical stirring of the micron-sized cockle shells powders in the presence of a non-toxic and non-hazardous biomineralization catalyst, dodecyl dimethyl betaine (BS-12). The method produced rod-shaped aragonite nanoparticles with the diameter of 20-30 nm with good reproducibility and without any additional impurities. This was confirmed by a combined analysis of variable pressure scanning electron microscopy (VPSEM), transmission electron microscopy (TEM), Fourier transmission infrared spectroscopy (FTIR), hermogravimetric analyzer (TGA), X-ray powder diffractometer (XRD) and an energy dispersive X-ray analyzer (EDX). The method should find potential applications in the industry for large scale synthesis of aragonite nanoparticles at low cost from an abundant natural resource such as cockle shells. The calcium carbonate nanoparticles in the aragonite phase were synthesized from the cheap and naturally abundant cockle shells. The pastes were developed from the cockle shell-based calcium carbonate nanoparticles. The composite pastes were used as bone repair in surgical applications. The cockle shell-based calcium carbonate nanoparticles were mixed with chitosan solution containing 2% acetic acid in a 250 ml glass beaker. The paste mixture was mixed using a multi-system hot plate mechanical stirrer with magnetic stirrer bar. The mixture clumped together and gave a homogeneous mesh like appearance. The paste was characterized by the Field Emission Scanning Electron Microscopy (FESEM), an Energy Dispersive X-ray Analyzer (EDXA), a Fourier transform infrared (FT-IR) spectrophotometer, an X-ray Powder Diffractometer (XRD), a thermogravimetric Analyzer (TGA), an Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) and Phosphate Buffer Saline Medium (PBS). The biocompatible and bioabsorbable pastes were developed from cockle shell-based nano calcium carbonate. The developed paste was evaluated in vivo using a rabbit model. The paste was compared functionally from the pastes of cockle shell-based micron sized calcium carbonate and commercial calcium carbonate respectively. Twelve rabbits which were divided into three groups (n=4) were used for the in vivo evaluation. The first,second and third groups were used for the paste of cockle shell-based nano calcium carbonate, cockle shell-based micron sized calcium carbonate and commercial calcium carbonate, respectively. One bone hole with 5 mm diameter was created on the medial surface of the proximal extremity of both left and right tibia. The left hole was left empty and acted as negative control while the right hole was treated with the paste implantation. After implantation, the paste effectiveness was evaluated by radiographic, biochemical, gross and histological examination. The dynamic cockle shell-based nanocomposite biomaterial bone paste showed excellent bone healing performance in the right bone holes as compared to the micron sized cockle shellbased calcium carbonate paste, commercial calcium carbonate paste and many previously prepared bone pastes. This novel bone paste can be potential for biomaterial industry, human and veterinary medicine.